A study on traffic signal waiting model using queuing theory - Lee, Joong Hoon; Yoon, Hyuck Joong; Chung, Tae Sun (Lecture Notes in Electrical Engineering, 2018)
This study analyzed the traffic situation by focusing on the characteristics of the customer after gaining idea from the ghost congestion phenomenon which is still congested even if the cause disappears once the congestion starts. We have developed a model that can quantitatively analyze queuing theory to apply to traffic situation. It is difficult to apply the queuing theory because the number of cars leaving the unit per hour varies greatly depending on the situation. Therefore, this study designed the model reflecting the variables that can occur in the actual traffic situation and obtained the throughput according to the situation. Simulation was carried out to verify the validity of the model. The concept of individual throughput for each customer was introduced, and the relation with the throughput was expressed through formulas. This research is useful in studying systems that have to reflect the characteristics of individual customers, or where interactions among customers play a large part in queuing.
Keywords: Individual customers; Large parts; Queuing theory; Simulation; Traffic situations; Waiting-time; Queuing theory; Simulation; Traffic control; Waiting time